Filantropi Islam dan Aktivisme Sosial Berbasis Pesantren di Pedesaan - Hilman Latief (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2012)
This article discusses the extent to which pesantren in a rural area finances its activities and operates social programs by revitalizing Islamic philantropic scheme. By way of a case study in a village at Kulonprogo District-Yogyakarta, where a small Muhammadiyah pesantren, which is Darul ‘Ulum, has been operating since the 1930s, this article suggests that the ability of this pesantren in engaging the villagers in religious and social activities has made this pesantren survives until now. Unlike other pesantrens, notably in urban areas, pesantren Darul ‘Ulum functions as an educational institution that provides an opportunity to thus students coming from low-income households, including orphanages to study. This paper asks to what extent a small pesantren in a rural area can resolve its budget constrains, how community supports and the culture of giving can, or cannot, underpine pesantren’s social and educational activities, and what sort of challenges for this pesantren to incease its institutional capacity? Keywords: pesantren, philantrophy, community innitiatives